2019
DOI: 10.3390/md17100546
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin Modulation of Signaling Pathways That Regulate Autophagy

Abstract: Autophagy is a lysosomal pathway that degrades and recycles unused or dysfunctional cell components as well as toxic cytosolic materials. Basal autophagy favors cell survival. However, the aberrant regulation of autophagy can promote pathological conditions. The autophagy pathway is regulated by several cell-stress and cell-survival signaling pathways that can be targeted for the purpose of disease control. In experimental models of disease, the carotenoid astaxanthin has been shown to modulate autophagy by re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 137 publications
(161 reference statements)
1
33
1
Order By: Relevance
“…AST can ameliorate cell apoptosis via more than one pathway, including ERK, NF-κB, and PI3K/Akt [27,[57][58][59]. Among these, the PI3K/Akt pathway is a prominent regulator of numerous proteins involved in cell survival through profound antioxidative and antiapoptotic actions [60].…”
Section: Discussionmentioning
confidence: 99%
“…AST can ameliorate cell apoptosis via more than one pathway, including ERK, NF-κB, and PI3K/Akt [27,[57][58][59]. Among these, the PI3K/Akt pathway is a prominent regulator of numerous proteins involved in cell survival through profound antioxidative and antiapoptotic actions [60].…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in biological properties of antioxidants such as carotenoids have suggested that these compounds are not only able to prevent but also able to ameliorate diabetes and its subsequent complications [6]. In particular, astaxanthin (ASX) (3,3 -dihydroxy-β, β -carotene-4,4 -dione), a xanthophyll carotenoid [7], has been reported to exhibit multiple biological activities including modulation of OS and inflammation through free radical quenching [8] and activation of endogenous antioxidant systems via modulation of gene expression [9,10] and has numerous advantages compared to some other carotenoids. Due to its unique structure, ASX is incorporated in the lipid bilayer of cellular membranes, without damaging it, and prevents lipid-based oxidation [11].…”
Section: Introductionmentioning
confidence: 99%
“…In colorectal cancer cells, EUG was identi ed as proautophagic compound [62], where the active fraction of clove (oleanonic acid and eugenol) increased LC3B I and II and Beclin-1 protein expression. AST modulates the signaling pathways that regulate autophagy [63], either by stimulation as shown in an experimental model of non-alcoholic fatty liver disease [64], or by inhibition as shown in the pancreas by inhibiting the JAK/STAT3 pathway [65]. Also the anti-oxidant and reactive oxygen scavengining activities of EUG [66] and AST [67] during DOX treatment may explain for the classical autophagic inhibition usually observed in that context with other anti-oxidant compounds [68].…”
Section: Discussionmentioning
confidence: 99%